Low-VOC (volatile organic compound) environment-friendly end-capped sulfydryl silane as well as preparation method and application thereof
By developing a low VOC environmentally friendly end-capped mercaptosilane, the problem of existing rubber additives releasing a large amount of alcohol when mixed with fillers is solved, and the effect of improving the reinforcing effect of fillers and improving the performance of vulcanized rubber is achieved. At the same time, the VOC emissions are reduced and environmental protection is improved.
Patent Information
- Application Number
- CN202411873816.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
AI Technical Summary
Existing rubber additives such as Si69 and Si75 will release a large amount of alcohol when mixed with fillers, resulting in environmental pollution and health risks. At the same time, their scorching time is short and their functions are single, making it difficult to meet the requirements of the rubber industry.
A low VOC environmentally friendly end capped mercaptosilane has a molecular structure that reduces the activity of silane organic functional groups by replacing short-chain alkoxy groups with long-chain linear alkyl polyether alcohols, thereby reducing the possibility of early scorching of the gel and reducing VOC emissions.
This silane can improve the reinforcement effect of fillers such as white carbon black, improve the dynamic mechanical properties and anti-charging properties of vulcanized rubber, reduce the production of volatile alcohols, improve environmental protection, and is suitable for various rubber formulas.
Smart Images

Figure CN119661578A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a low-VOC environmentally friendly blocked mercaptosilane and a preparation method and application thereof, belonging to the technical field of rubber additives. Background Art
[0002] In order to improve the various physical and mechanical properties of rubber, some inorganic fillers are generally added to the rubber formula, including white carbon black, carbon black, calcium carbonate, talc, clay, etc., among which carbon black and white carbon black are the most common. The interaction of the cross-linked network formed by carbon black, white carbon black and rubber can effectively improve the reinforcing effect of the filler. White carbon black is an active ultra-fine silica particle, the chemical name is hydrated amorphous silica or colloidal silica, it is an important fine inorganic chemical product. White carbon black has a special surface structure (with surface hydroxyl groups and adsorbed water), a special particle morphology (small particles, large specific surface area, etc.) and unique physical and chemical properties. It has many advantages that inorganic materials do not have. However, since the polysiloxane group inside white carbon black and the active silanol group on the outer surface are very easy to adsorb water, it is hydrophilic, so it is difficult to wet and disperse in the organic phase. Moreover, due to the presence of hydroxyl groups on its surface, the surface energy is large, and the aggregates always tend to condense, thus affecting the application performance of the product. Therefore, when using it, it is usually necessary to perform surface modification on silica to improve its application effect, increase its added value, and thus expand the application field of the product.
[0003] Modifying the surface of silica with a silane coupling agent is a relatively common modification method. For example, patents CN112011092B, CN102220036A, and CN107266941A all provide methods for modifying silica with a silane coupling agent. The dispersibility of the modified silica obtained by these methods has been improved to a certain extent, but there is still room for improvement.
[0004] In the market, silanes such as bis[3-(triethoxysilyl)propyl]tetrasulfide Si69 and bis[3-(triethoxysilyl)propyl]disulfide Si75 are usually used in filler-filled rubber to achieve good reinforcement effects. However, traditional rubber silanes Si69 and Si75 have short scorch times and single functions, making it difficult to meet the requirements of the rubber industry. At the same time, since Si69 and Si75 have three alkoxy substituents on their silicon atoms, trimethoxysilane and triethoxysilane are usually used, which will release a large amount of corresponding alcohols - methanol and ethanol - during or after mixing with fillers, polluting the environment of the processing workshop and causing a certain degree of damage to the health of workers.
[0005] In order to solve the above problems, some alternatives have appeared on the market. For example, Chinese patent No. CN101445620A discloses a benzothiazole mercaptosilane. Although this additive solves the scorch problem, since the additive still has three alkoxy substituents on the silicon atom, a large amount of alcohol will still be released during or after mixing with the filler. Summary of the invention
[0006] In view of the deficiencies in the above prior art, the present invention provides a new type of low-VOC environmentally friendly blocked mercaptosilane, which is used in rubber compounds to improve the reinforcing effect of fillers such as white carbon black, improve the dynamic mechanical properties and anti-scorch performance of vulcanized rubber, and produces less volatile alcohol and has good environmental protection.
[0007] The present invention provides a low-VOC environmentally friendly capped mercaptosilane, wherein the silane has a molecular structure shown in the following formula I: In Formula I: R1 is methyl or ethyl.
[0008] R2 is a straight chain alkyl ether group, such as -(CH2CH2O) n -C m H 2m+1 , wherein m is an integer from 3 to 15, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15. n is an integer from 3 to 20, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.
[0009] R2' is the same group as R1 or the same group as R2, for example, methyl, ethyl or -(CH2CH2O) n -C m H 2m+1 , wherein m is an integer from 3 to 15, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15; n is an integer from 3 to 20, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.
[0010] R3 is a C1-C30 alkylene group, such as a methylene group, an ethylene group, a propylene group, or a C4-C30 straight-chain alkylene group; R4 is a C3-C20 alkyl group, which can be a straight chain alkyl group or a branched chain alkyl group, which can be represented by -C k H 2k+1, wherein k is an integer from 3 to 20, for example, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20.
[0011] Preferably, the low VOC environmentally friendly capped mercaptosilane has the structural formula shown below: .
[0012] Preferably, the low VOC environmentally friendly capped mercaptosilane has the structural formula shown below: Furthermore, the present invention also provides a method for preparing the above-mentioned low-VOC environmentally friendly capped mercaptosilane, which comprises the following steps: (1) reacting a chloroalkyltrialkoxysilane of formula a with a linear alkyl polyether alcohol of formula b in the presence of a catalyst A to obtain an intermediate c; (2) reacting the alkyl acyl chloride of formula d with sodium sulfide or sodium hydrosulfide in the presence of a catalyst B to obtain an intermediate e; (3) reacting the intermediate c and the intermediate e in the presence of a catalyst B to obtain a low VOC environmentally friendly capped mercaptosilane of formula Ⅰ; ; In formula a, formula b, formula c and formula d, the definitions of R1, R2, R2', R3 and R4 are consistent with those in formula I.
[0013] Furthermore, in step (1), the molar ratio of chloroalkyltrialkoxysilane to linear alkyl polyether alcohol is different, and the structure of the obtained intermediate c is different. When the molar ratio of chloroalkyltrialkoxysilane to linear alkyl polyether alcohol is 1:0.9-1.1, R2' in the intermediate c is R 1, The structural formula of intermediate c is When the molar ratio of chloroalkyltrialkoxysilane to linear alkyl polyether alcohol is 1:2-2.1, R2' in the intermediate c is R 2, The structural formula of intermediate c is .
[0014] Furthermore, in step (1), the catalyst A is at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium methoxide, sodium ethoxide, zinc acetate, zinc octanoate, zinc isooctanoate, zinc naphthenate, dibutyltin dilaurate, tin tartrate, stannous octanoate, cobalt naphthenate, cobalt isooctanoate, n-butyl titanate, tetraisopropyl titanate, organic titanium chelate and aluminate. The organic titanium chelate refers to a complex formed by an organic substance containing a carbon-hydrogen skeleton and titanium ions, and examples thereof include tert-butyl isobutyl titanium chelate and the like.
[0015] Preferably, the catalyst A is a mixture of an organic titanium chelate and tetraisopropyl titanate. More preferably, the mass ratio of the organic titanium chelate to tetraisopropyl titanate is 1:1-4.
[0016] Furthermore, in step (1), the amount of catalyst A used is 0.5% to 5% by mass of the chloroalkyltrialkoxysilane, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.
[0017] Furthermore, in step (1), the reaction is carried out under negative pressure, and the pressure is -30 KPa to 0 KPa, for example, -30 KPa, -20 KPa, -10 KPa, -5 KPa, 0 KPa.
[0018] Further, in step (1), the reaction temperature is 30 to 180°C, for example 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, and the reaction time is 1 to 24 hours, for example 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h.
[0019] Furthermore, in step (1), there is no particular requirement for the order in which the reaction raw materials are added.
[0020] Furthermore, in step (1), after the reaction, the crude intermediate c obtained can be directly used in the next reaction.
[0021] Furthermore, in step (2), the molar ratio of sodium sulfide to alkyl acyl chloride is at least 1:1, such as 1:1-1.1. The molar ratio of sodium hydrosulfide to alkyl acyl chloride is at least 2:1, such as 2-2.1:1.
[0022] Furthermore, in step (2), the catalyst B is at least one of chain polyethylene glycol, chain polyethylene glycol dialkyl ether (CAS No.: 24991-55-7), benzyl triethyl ammonium chloride (TEBA), tetrabutyl ammonium bromide (TBAB), tetrabutyl ammonium chloride, tetrabutyl ammonium hydrogen sulfate, trioctyl methyl ammonium chloride, dodecyl trimethyl ammonium chloride, tetradecyl trimethyl ammonium chloride, pyridine, tributylamine, quaternary ammonium base and quaternary phosphonium salt catalysts. The molecular weight of the chain polyethylene glycol is 200-800.
[0023] Preferably, catalyst B is a mixture of chain polyethylene glycol and tetrabutylammonium bromide (TBAB). More preferably, the mass ratio of chain polyethylene glycol to tetrabutylammonium bromide is 1:1-4.
[0024] Furthermore, in step (2), the amount of catalyst B used is 0.5% to 5% by mass of the alkyl acid chloride, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, and 5%.
[0025] Furthermore, in step (2), sodium sulfide or sodium hydrosulfide is introduced in the form of an aqueous solution, the concentration of the solution is 5 to 50 wt%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, and water is used as the reaction medium.
[0026] Furthermore, in step (2), nitrogen replacement is performed before the reaction. There is no special requirement for the order of adding the raw materials.
[0027] Furthermore, in step (2), the reaction is carried out under negative pressure, and the pressure is -30 KPa to 0 KPa, for example, -30 KPa, -20 KPa, -10 KPa, -5 KPa, 0 KPa.
[0028] Furthermore, in step (2), the reaction temperature is 0 to 80°C, for example, 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, and the reaction time is 0.5 to 5 hours, for example, 0.5h, 1h, 2h, 3h, 4h, 5h.
[0029] Furthermore, in step (2), after the reaction, the aqueous phase is removed by simple liquid separation, and the oil phase is the crude intermediate e.
[0030] Furthermore, in step (3), intermediate c and intermediate e are added in a molar ratio of chloroalkyltrialkoxysilane to alkylacyl chloride of 1:0.9-1.1.
[0031] Furthermore, in step (3), the definition and selection of the catalyst B used are the same as described above.
[0032] Furthermore, in step (3), the catalyst B is preferably a mixture of chain polyethylene glycol and tetrabutylammonium bromide, and the mass ratio of the chain polyethylene glycol to tetrabutylammonium bromide can be 1:1-4.
[0033] Furthermore, in step (3), the amount of catalyst B used is 0.1% to 2.5% of the mass of the intermediate e, for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%.
[0034] Furthermore, in step (3), nitrogen replacement is performed before the reaction. There is no special requirement for the order in which the raw materials are added to the reaction.
[0035] Furthermore, in step (3), the reaction is carried out under negative pressure, and the pressure is -30 KPa to 0 KPa, for example, -30 KPa, -20 KPa, -10 KPa, -5 KPa, 0 KPa.
[0036] Furthermore, in step (3), the reaction temperature is 50 to 120°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, and the reaction time is 1 to 10 hours, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h.
[0037] Furthermore, in step (3), after the reaction is completed, the reaction liquid is separated to take the upper organic phase, and the organic phase is added with a water-absorbing resin to remove water. After the water is removed, the filtrate is filtered, and the filtrate is distilled under reduced pressure to remove the residual small molecular alcohol substances, and then filtered to remove the solid impurities. The final residue is the target product.
[0038] The silaneoxy group of the low-VOC environmentally friendly capped mercaptosilane molecule of the present invention is replaced by a long-chain straight-chain alkyl polyether alcohol to replace one or two short-chain alkoxy groups. The substituted long-chain straight-chain alkyl polyether oxygen group can reduce the activity of the silane organic functional group through physical coating, thereby reducing the possibility of premature scorching of the rubber compound during the mixing process and improving the processing performance of the rubber compound; at the same time, the straight-chain alkyl polyether alcohol generated after the substituted long-chain straight-chain alkyl polyether oxygen group is modified on white carbon black has a high boiling point and is not easy to volatilize, thereby reducing the emission of VOC in the production process and having good environmental protection.
[0039] The low-VOC environmentally friendly blocked mercaptosilane of the present invention can be applied to natural rubber and various synthetic rubber formulations, and is an environmentally friendly multifunctional rubber additive. While reducing VOC emissions, it can also improve the filler reinforcement effect, improve the dynamic mechanical properties, physical mechanical properties, and vulcanization properties of the vulcanized rubber, and extend the scorch time of the rubber compound. When it is applied to the tread rubber of a radial tire, it can improve the wet skid resistance of the tread rubber and reduce its rolling resistance. By adsorbing it on an inert organic or inorganic carrier, or pre-reacting with an organic or inorganic carrier, it can be applied to different fields such as preparing molded products, pneumatic tires, tire treads, hoses, transmission belts, seals, and shock absorbing elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The mass spectrum of the product obtained in Example 1 is shown in FIG. DETAILED DESCRIPTION
[0041] The following is a description of exemplary embodiments of the present invention, including various details of the embodiments of the present invention to facilitate understanding, which should be considered as merely exemplary. Therefore, it should be recognized by those of ordinary skill in the art that various changes and modifications may be made to the embodiments described herein without departing from the scope and spirit of the present invention. Similarly, for the sake of clarity and conciseness, descriptions of well-known functions, operations and structures are omitted in the following description. The methods described in the following embodiments, unless otherwise specified, are conventional methods; the materials, unless otherwise specified, can be obtained from commercial sources.
[0042] In the following examples and comparative examples, unless otherwise specified, the concentrations are all mass percentage concentrations.
[0043] Example 1 1. Place 1 mol (240.8 g) of chloropropyltriethoxysilane and 2 mol (813.2 g) of polypentyl glycol monolaurate in a three-necked flask, add 3 g of catalyst dibutyltin dilaurate, evacuate to a pressure (gauge pressure) of -30 KPa, then heat to 80 ° C and react for 4 hours to obtain a crude intermediate c in a light yellow transparent liquid state; 2. Place 560 g of 20% sodium hydrosulfide aqueous solution and 3 g of benzyltriethylammonium chloride in a three-necked flask, replace with nitrogen, evacuate to -30 KPa, then add 1 mol (162.7 g) of octanoyl chloride, react at 40 ° C for 5 hours, separate the liquid and take the organic phase to obtain a crude intermediate e; 3. Add all the crude intermediate c obtained in step 1 and all the crude intermediate e obtained in step 2 into a three-necked flask, add 2 g of benzyltriethylammonium chloride, replace with nitrogen, evacuate to a pressure of -30 KPa, then heat to 80 ° C and react for 8 hours. Separate the reaction solution and take the top organic phase as the crude product. Add 5% of its mass of water-absorbing resin to the crude product to remove water. After removing water, filter to remove the water-absorbing resin. Distill the filtrate under reduced pressure at -0.095 MPa and 100 ° C to remove residual small molecular alcohol substances in the crude product, and then centrifuge to remove solid impurities to obtain 1128 g of a transparent light yellow liquid.
[0044] The mass spectrum of the product is Figure 1 As shown, its structural formula is as follows: Example 2 The operation was carried out according to the method of Example 1, except that in step 1, the amount of polypentylene glycol monolauryl ether used was 1 mol. The final residue was 740 g of the target product, and the structural formula of the product was as follows: Example 3 The operation was carried out according to the method of Example 1, except that: in step 1, 3g of dibutyltin dilaurate was replaced by 0.6g of tert-butyl isobutyl chelated titanium and 2.4g of tetraisopropyl titanate; in step 2, 3g of benzyltriethylammonium chloride was replaced by 0.6g of chain polyethylene glycol (molecular weight 600-800) and 2.4g of tetrabutylammonium bromide (TBAB); in step 3, 2g of benzyltriethylammonium chloride was replaced by 0.4g of chain polyethylene glycol (molecular weight 600-800) and 1.6g of tetrabutylammonium bromide (TBAB). The obtained product was the same as that in Example 1, and the mass of the target product was 1137g.
[0045] Example 4 The operation was carried out according to the method of Example 1, except that: in step 1, 3g of dibutyltin dilaurate was replaced by 3g of cobalt isooctanoate; in step 2, 3g of benzyltriethylammonium chloride was replaced by 3g of tetradecyltrimethylammonium chloride; in step 3, 2g of benzyltriethylammonium chloride was replaced by 2g of tetradecyltrimethylammonium chloride. The obtained product was the same as that in Example 1, and the mass of the target product was 1012g.
[0046] Example 5 The operation was carried out according to the method of Example 1, except that: in step 1, the pressure was evacuated to -10 KPa, and then the temperature was raised to 120°C for 4 hours; in step (2), the temperature was raised to 60°C for 5 hours; in step 3, the temperature was raised to 100°C for 8 hours. The obtained product was the same as that in Example 1, and the mass of the target product was 1132 g.
[0047] Example 6 The operation was carried out according to the method of Example 1, except that in step 1, 1 mol of chloropropyltriethoxysilane was replaced with 1 mol of chloropropyltrimethoxysilane. The obtained product was a transparent light yellow liquid with a mass of 1117 g and the structural formula was as follows: Example 7 The operation was carried out according to the method of Example 1, except that in step 1, 2 mol of polypentylene glycol monolauryl ether was replaced with 2 mol of polypentylene glycol monooctyl ether. The obtained product was a transparent light yellow liquid with a mass of 1075 g and a structural formula as follows: Example 8 The operation was carried out according to the method of Example 1, except that in step 2, 1 mol of octanoyl chloride was replaced with 1 mol of dodecyl chloride. The other aspects were the same, and the obtained product was a transparent light yellow liquid with a mass of 1186 g.
[0048] The product structure is: Example 9 The operation was carried out according to the method of Example 1, except that in step 2, 560 g of 20% sodium hydrosulfide solution was replaced with 390 g of 20% sodium sulfide solution. The obtained product was the same as that of Example 1, with a mass of 1109 g.
[0049] Comparative Example 1 The operation was carried out according to the method of Example 1, except that in step 1, no catalyst was added, and finally 1286 g of milky yellow-white turbid liquid was obtained.
[0050] Comparative Example 2 The operation was carried out according to the method of Example 1, except that in step 2, no catalyst was added, and finally 1341 g of milky yellow-white turbid liquid was obtained.
[0051] Comparative Example 3 The operation was carried out according to the method of Example 1, except that in step 3, no catalyst was added, and finally 1320 g of a milky yellow-white turbid liquid was obtained.
[0052] The purity and conversion rate of the products obtained in the above examples and comparative examples were calculated, wherein the purity was detected by gas chromatography, and the conversion rate was calculated as follows: Where: a is the purity of the product; w is the theoretical product mass; w´ is the actual product mass.
[0053] The purity and conversion rate of the products obtained in each embodiment and comparative example are shown in Table 1 below: It can be seen from Table 1 that the catalyst affects the conversion rate and purity of the product, and the combined catalyst in Example 3 has the best effect; the temperature affects the generation of by-products, thereby affecting the purity and conversion rate of the target product; sodium sulfide instead of sodium hydrosulfide will affect the purity and conversion rate of the target product.
Claims
1. A low VOC environmentally friendly capped mercaptosilane, characterized by: It has the structural formula shown in the following formula I: Where: R1 is methyl or ethyl; R2 is -(CH2CH2O) n -C m H 2m+1 , wherein m is an integer from 3 to 15, and n is an integer from 3 to 20; R2´ is R1 or R2; R3 is a C1-C30 alkylene group; R4 is a C3-C20 alkyl group.
2. A method for preparing the low VOC environmentally friendly blocked mercaptosilane according to claim 1, characterized in that The following steps are involved: (1) reacting a chloroalkyltrialkoxysilane of formula a with a linear alkyl polyether alcohol of formula b in the presence of a catalyst A to obtain an intermediate c; (2) reacting the alkyl acyl chloride of formula d with sodium sulfide or sodium hydrosulfide in the presence of a catalyst B to obtain an intermediate e; (3) reacting the intermediate c and the intermediate e in the presence of a catalyst B to obtain a low VOC environmentally friendly capped mercaptosilane of formula Ⅰ; ; In formula a, formula b, formula c and formula d, the definitions of R1, R2, R2', R3 and R4 are consistent with those in formula I.
3. The preparation method according to claim 2, characterized in that: In step (1), the molar ratio of chloroalkyltrialkoxysilane to linear alkyl polyether alcohol is 1:0.9-1.1 or 1:2-2.1; preferably, in step (2), the molar ratio of sodium sulfide to alkyl acyl chloride is 1:1-1.1, and the molar ratio of sodium hydrosulfide to alkyl acyl chloride is 2-2.1:
1.
4. The preparation method according to claim 2, characterized in that: In step (1), the catalyst A is at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium methoxide, sodium ethoxide, zinc acetate, zinc octoate, zinc isooctanoate, zinc naphthenate, dibutyltin dilaurate, tin tartrate, stannous octoate, cobalt naphthenate, cobalt isooctanoate, n-butyl titanate, tetraisopropyl titanate, organic titanium chelate and aluminate, preferably a mixture of organic titanium chelate and tetraisopropyl titanate.
5. The preparation method according to claim 2 or 4, characterized in that: In step (1), the amount of catalyst A used is 0.5% to 5% of the mass of the chloroalkyltrialkoxysilane; preferably, in step (1), the reaction temperature is 30 to 180° C., and the reaction time is 1 to 24 hours.
6. The preparation method according to claim 2, characterized in that: In step (2) and step (3), catalyst B is at least one of chain polyethylene glycol, chain polyethylene glycol dialkyl ether, benzyltriethylammonium chloride, tetrabutylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, trioctylmethylammonium chloride, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, pyridine, tributylamine, quaternary ammonium base and quaternary phosphonium salt catalysts, preferably a mixture of chain polyethylene glycol and tetrabutylammonium bromide.
7. The preparation method according to claim 2 or 6, characterized in that: In step (2), the amount of catalyst B used is 0.5% to 5% of the mass of the alkyl acyl chloride; preferably, in step (3), the amount of catalyst B used is 0.1% to 2.5% of the mass of the intermediate e; preferably, in step (2), the reaction temperature is 0 to 80° C., and the reaction time is 0.5 to 5 hours.
8. The preparation method according to claim 2, characterized in that: In step (3), intermediate c and intermediate e are added in a molar ratio of chloroalkyltrialkoxysilane to alkylacyl chloride of 1:0.9-1.1; preferably, in step (3), the reaction temperature is 50-120° C. and the reaction time is 1-10 hours.
9. The preparation method according to claim 2, characterized in that: In steps (1), (2) and (3), the reactions are all carried out under negative pressure, and the pressure is -30 KPa to 0 KPa.
10. Use of the low VOC environmentally friendly blocked mercaptosilane according to claim 1 as a rubber additive.
Citation Information
Patent Citations
Multi-functional rubber additive and method for preparing same
CN101445620A
Method for preparing white carbon black modified by silane coupling agent
CN102220036A
Modification method of nano white carbon black used as rubber filler
CN107266941A
Methods for modifying silica
CN112011092B
Low-volatility benzothiazolyl mercaptosilanes and preparation method thereof
CN102344462A
Cited By
Mixing process of rubber compound and application of octanoyl thiopropyltriethoxysilane
CN122344351A
Low-voc environment-friendly silane and synthesis method and application thereof
CN122668158A